The structure and regulation of the Irish equine industries: Links to considerations of equine welfare - Collins J; Hanlon A; More SJ; Duggan V (Irish Veterinary Journal, 2008)
Abstract The equine industries in Ireland are vibrant and growing. They are broadly classified into two sectors: Thoroughbred racing, and sports and leisure. This paper describes these sectors in terms of governance, education and training in equine welfare, and available data concerning horse numbers, identification, traceability and disposal. Animal welfare, and specifically equine welfare, has received increasing attention internationally. There is general acceptance of concepts such as animal needs and persons' responsibilities toward animals in their care, as expressed in the 'Five Freedoms'. As yet, little has been published on standards of equine welfare pertaining to Ireland, or on measures to address welfare issues here. This paper highlights the central role of horse identification and legal registration of ownership to safeguard the health and welfare of horses.